Maintenance of Electric and Hybrid Vehicles - De Souza Araujo, Paulo Victor; Komlósi, István; Varga, Tamás Zoltán; Menyhárt, József (International Journal of Engineering and Management Sciences, 2020)
An electric car is a vehicle powered by one or more electric engines, utilizing energy stored within batteries that are rechargeable. The first register of a usable electrical vehicle dates from 1880s. A hybrid vehicle incorporates two or more different power types, including, e.g., gasoline engines and electric motor. The goal in this work is to present the overall overview of the structure of the electric, hybrid and electric-hybrid vehicles, advantages and disadvantages of these types, the main points to focus when maintaining these and the challenges involved in its production and maintenance.